A decolonial critique of private law and human rights. Issue 3 (2nd September 2018) - Zitzke, Emile
Abstract: Two approaches to private-law scholarship are critiqued in this article. The first problematic approach identified is that of 'private-law purism' that aims to segregate so-called 'proper' dominant private law from everything else. In its classical form, private-law purism involved purifying South African private law (which is largely built on Roman-Dutch foundations) from English influences. In its contemporary form, private-law purism involves shielding dominant South African private law from human rights. The key issue with classical and contemporary purism illustrated in this article is that purism is built on a racist ideology that promotes epistemicide, originally brought about by conquest. The second potentially problematic approach identified is 'transformative private law' that aims to push private law in a more egalitarian direction through infiltrating the discipline with human rights. Although transformative private law is a significant rebellion against purism, the epistemic roots of human rights are perhaps as Western as dominant private law. Transformative private law thus has a neo-colonial flair. For that reason, a fusion of human rights with dominant private law will not necessarily result in a decolonial system of private law. Instead of the purist and transformative approaches to the study of private law, it is argued that Africanisation through conceptual decolonisation – a critical study of private law through African philosophy, not limited to the invocation of ideas with legal authority – could be one way of ensuring a more forceful response to the colonial problems of dominant private law and human rights.